Pelatihan Kader Tuberkulosis di Wilayah Kerja Puskesmas Bluto sebagai Upaya Penurunan Kasus - Anggraini Dwi Sensusiati; Alfian Nur Rosyid; Arina Dery Puspitasari (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Indonesia is the 3rd ranked country with the highest number of TB cases in the world, namely 845,000 cases in 2020. In the same year, the number of suspected TB in East Java was 42,922 cases and Sumenep Regency was in the 11th position with the most TB with 1,924 cases. Therefore, community service activities aim to carry out training for TB cadres at the Bluto Health Center as an effort to reduce TB cases. Community service activities are carried out from April to July 2022. Activities begin with planning, obtaining permits, coordination meetings, training preparations, conducting webinars, conducting face-to-face training, pre-test and post-test evaluations. Activities went well. The impact of implementing training activities was in the form of 93% of cadres experiencing an increase in knowledge and the other 7% experiencing a decrease in knowledge. These good results can be used as a basis for local health workers to continue activities to increase the knowledge and skills of cadres using the lecture method; question and answer; health promotion media in the form of videos; and direct practice. Cadres can also use the same method to educate the target community regarding TB, how to prevent and treat it.